2021
DOI: 10.1007/s13679-021-00458-6
|View full text |Cite
|
Sign up to set email alerts
|

Safe Surgery During the COVID-19 Pandemic

Abstract: Purpose of Review Coronavirus Disease-2019 (COVID-19) has had an enormous impact on all aspects of healthcare, but its effect on patients needing surgery and surgeons has been disproportionate. In this review, we aim to understand the impact of the pandemic on surgical patients and teams. We compiled the emerging data on pre-operative screening methods, vaccinations, safe-surgery pathways and surgical techniques and make recommendations for evidence-based safe-surgical pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 80 publications
0
5
0
3
Order By: Relevance
“…This finding contrasts with a study which showed COVID-19 has had an enormous impact on patients needing surgery due to increased risk for patients and staff. [25] It would be reasonable to suggest that restrictive hospital COVID-19 protocols would have an impact on the stress level. However, it can be concluded that the high ranking of stress from restricted visitation of spouse, family, and friends was not due to the impact of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with a study which showed COVID-19 has had an enormous impact on patients needing surgery due to increased risk for patients and staff. [25] It would be reasonable to suggest that restrictive hospital COVID-19 protocols would have an impact on the stress level. However, it can be concluded that the high ranking of stress from restricted visitation of spouse, family, and friends was not due to the impact of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Essas condutas ampliam a segurança para os pacientes e para equipe de saúde (34) . Portanto, as investigações (40)(41)(42) recomendam primeiramente realizar a triagem dos pacientes, com anamnese direcionada à identificação de sinais e sintomas da Covid-19. Além disso, recomendam também a realização de testes diagnósticos moleculares ou imunológicos e, quando não disponíveis em tempo hábil, a consideração do paciente como possível portador da Covid-19 (41)(42) .…”
Section: Discussionunclassified
“…Portanto, as investigações (40)(41)(42) recomendam primeiramente realizar a triagem dos pacientes, com anamnese direcionada à identificação de sinais e sintomas da Covid-19. Além disso, recomendam também a realização de testes diagnósticos moleculares ou imunológicos e, quando não disponíveis em tempo hábil, a consideração do paciente como possível portador da Covid-19 (41)(42) . Estudo (33) também recomenda a tomografia computadorizada de tórax como uma possibilidade suplementar na triagem do paciente.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As for the recommendations on surgical procedures, these range from the selection of the anesthetic modality, the adequate manipulation of the airways, to the execution of the surgical technique (12,(20)(21)24) . In the context of the Covid-19 pandemic, the main objective is to reduce the production and dispersion of With regard to the surgical modality, i.e., minimally invasive or open surgery, there are no clear recommendations in the literature on which technique produces fewer airborne particles (40)(41)(42)(43) . The included literature identifies thoracic, neurological, otorhinolaryngological, maxillofacial, and laparoscopic surgeries as procedures related to the high production of air particles (20)(21)29) .…”
Section: Recommendationsmentioning
confidence: 99%